Treatment of complicated urinary tract infections with lomefloxacin compared with that with trimethoprim-sulfamethoxazole. - Nicolle, L E (1994)
The efficacy of lomefloxacin given at 400 mg once daily for 14 days compared with that of trimethoprim-sulfamethoxazole at 160 and 800 mg, respectively, given twice daily for 14 days in the treatment of symptomatic complicated urinary tract infections was studied in a prospective, randomized, single-blind multicenter study. A total of 133 subjects presenting with signs and symptoms of urinary tract infection and an underlying abnormality consistent with complicated urinary tract infection were enrolled in the study. Bacteriologic cure was significantly better in 68 subjects randomized to lomefloxacin than in 65 subjects randomized to trimethoprim-sulfamethoxazole at short-term follow-up (88 versus 52%; 95% confidence intervals [CIs] 77 and 94% and 39 and 65%, respectively) this difference was no longer significant at long-term follow-up (64 versus 47%; CIs, 52 and 75% and 32 and 57%, respectively). Clinical outcomes were similar for both therapeutic regimens at short- and long-term follow-ups. The organisms that infected the subjects pretherapy were more frequently resistant to trimethoprim-sulfamethoxazole, and drug therapy was discontinued more frequently in subjects treated with trimethoprim-sulfamethoxazole because of adverse antimicrobial effects. In secondary analyses, outcomes did not differ with age or underlying genitourinary abnormality.(ABSTRACT TRUNCATED AT 250 WORDS)